The Development of Women’s Epistolary Writing in Arabic Literature - allata, tladjia; Mokhtari, Fatima (El Omda in Linguistics and Discourse Analysis, 2023)
Modern literary and critical studies have always paid attention to a variety of prose arts, but our interest in the novel and the story was clear and tangible, in a way that almost dominates other prose arts such as the article, description of the journey, theatrical and the like, some of them even called this era the era of the novel, the era of the story, but They claimed that the novel is the modern Arab divan, and in light of this interest, the feminist transmission is absent, and its role is marginalized, so it hardly finds a market for it at a time when people turned to other arts, from here came this paper to prove the status of this ancient literary art, and to highlight its role, She talks about his reality.